The correlation analysis between airflow and oxygen saturation in obstructive sleep apnea events using correlation function - Sezgin, Necmettin; Kirbas, Gokhan; Akin, Mehmet (IEEE, 2007)
Diagnosis of Sleep apnea syndrome (SAS) is currently performed by a full night polysomnography study at sleep laboratories. The majority of apnea patients are treated by constant positive airway pressure (CPAP) device. The apnea can be broadly classified into three types: obstructive sleep apnea (OSA), central sleep apnea (CSA) and mixed sleep apnea (MSA). During OSA, the airway is blocked while respiratory efforts continue. During CSA the airway is open, however there are no respiratory efforts. There is an efficient correlation between airflow and SaO(2) in sleep apnea events. In this paper, it is aimed to find the correlation degree between airflow and oxygen saturation by using cross corelation function in obstructive sleep apnea events. In the future studies the correlation will be able to detect the sleep apnea and controlling CPAP device automatically as an intelligent system.
Keywords: correlation; SAS; OSA; airflow; SaO2; ALCOHOL; DIAGNOSIS; AROUSAL; NECK; Computer Science; Engineering; Telecommunications